Analysis of English Skill Tests for Grade VII Students Based on Language Assessment Principles - Yolanda Jesica Sitanggang; Tessaria Simorangkir; Angel Lamtama Sihaloho; Rotua Sinta Marito Pakpahan; Dumaris E Silalahi (STKIP Taman Siswa Bima, 2025)
This study evaluates English assessment instruments for Grade VII students at SMP Swasta Taman Asuhan based on five principles of language assessment: practicality, reliability, validity, authenticity, and washback. A mixed-method research design was employed, combining quantitative analysis of test validity and reliability with qualitative evaluation through classroom observations. The study involved 20 students and assessment tasks for writing, reading, listening, and speaking. The findings revealed that practicality was achieved as all tests were implemented efficiently using available resources and time. Reliability analysis showed high internal consistency for speaking and listening (Cronbach’s Alpha = 0.94), writing (0.86), and moderate reliability for reading (0.59). Validity analysis using Pearson Product Moment indicated that most essay items in all skills were valid, while several multiple-choice items in writing and reading were invalid. Authenticity was evident through tasks relevant to students' real-life experiences. Washback was positive, as the assessments encouraged meaningful language use and provided valuable instructional feedback. These results affirm that the instruments are generally effective but require revision in certain areas.